Analisis Pentingnya Peran Moderasi Beragama di Era Digital - Utami, Lutfi Ayu fadhilah; Sulistiorini, Tri; Lestari, Ira (Moderatio: Jurnal Moderasi Beragama, 2023)
This study aims to describe the phenomenon of religious moderation in the digital era. This research uses a qualitative descriptive method with the type of library research or literature study to collect, read, record, process, and analyze the main topics in this research which are sourced from documents, reports, books, research journals, articles, scientific magazines and other data that support this research. This research aims to analyze the role of religious moderation towards conflicts that occur in the community in order to maintain the welfare and peace of the people. The results showed that in this digital era it is necessary to apply the attitude of religious moderation to avoid various conflicts, both inter-religious conflicts and conflicts in society. According to research conducted by Yusuf Al-Qardhawi, many internal conflicts of Muslims today are caused by excessive religious patterns or it can be said that some other groups of Muslims have not been able to place things in their place. From this attitude raises the attitude of fanaticism and blames the understanding that is different from their beliefs. Believing in God by obeying religion and avoiding His prohibitions is indeed an obligation that must be carried out for religious people, but religious patterns that are too extreme to cause a religious conflict are also prohibited, for that religious moderation is needed.